Substantial Increases in the Water and Sediment Fluxes in the Headwater Region of the Tibetan Plateau in Response to Global Warming. Issue 11 (7th June 2020) - Li, Dongfeng; Li, Zhiwei; Zhou, Yinjun; Lu, Xixi
Abstract: The long‐term effects of increased temperatures on sediment fluxes in cold regions remain poorly investigated. Here, we examined the multidecadal changes in runoff and sediment fluxes in the Tuotuohe River, a headwater river of the Yangtze River on the Tibetan Plateau (TP). The sediment fluxes and runoff increased at rates of 0.03 ± 0.01 Mt/yr (5.9 ± 1.9%/yr) and 0.025 ± 0.007 × km 3 /yr (3.5 ± 1.0%/yr) from 1985 to 2016, with net increases of 135% and 78% from 1985–1997 to 1998–2016, respectively. The increases are primarily due to warming temperature (+1.44°C) and intensified glacier‐snow‐permafrost melting, with enhanced precipitation (+30%) as a secondary cause. Sediment fluxes are much more susceptible to climate warming than runoff in this undisturbed cold environment. The substantially increased sediment fluxes from the headwater region could threaten the numerous constructed reservoirs and influence the aquatic ecosystems of the TP and its marginal areas. Key Points: Runoff and sediment fluxes and their interannual variabilities increased substantially in this undisturbed cold environment Climate warming is likely the primary reason for the increased sediment fluxes and enhanced precipitation plays a secondary role The substantially increased sediment fluxes from the headwaters have important implications for downstream reservoirs and aquatic ecosystems